Make an in-depth study into the ways and extents to which the maritime industry may contribute to achieve related UN global goals (SDGs) - Chin, Melvin Yong An (Nanyang Technological University, 2021)
Sustainability Development Goals (SDGs) are a set of wide-ranging agenda agreed upon internationally in 2015 which aims to promote actions towards, social, economic, and environmental sustainability. The SDGs are anticipated to be achieved by 2030. The maritime industry is recognized as a key stakeholder that can play a huge role in contributing to the SDGs. The maritime industry plays a significant role to the achievement of SDGs as it is the lifeline of global economy. Therefore, this research paper seeks to establish the links between the related SDGs and the maritime industry. Current practices adopted by the maritime industry in achieving these SDGs will also be explored in the paper. A comprehensive literature review will then be carried out to understand the research gaps in this area of interest. To close the research gaps, a series of primary data such as interviews with industry professionals and secondary data such as industry journals, sustainability reports and websites will be collected from time to time to enhance the author’s knowledge in this area of interest. Finally, this research paper will also provide recommendations to illustrate the ways and extents in which the relevant maritime stakeholders can contribute to the 2030 Agenda for Sustainable Development.